The Benefits of Financial Ratios' as the Indocators of Future Bankruptcy on the Economic Crisis - Setia Mulyawan (UIN Sunan Gunung Djati Bandung, 2015)
It is proved that financial ratios can predict future bankruptcy even on high uncertainty conditions such as an economic crisis. The research indicates that the accuracy of prediction is more increasing in line with a coming bankruptcy.The result of the research shows that four years before a corporate becomes bankrupt there have been significant differences of financial ratios between bankrupt company and sustained one. The ratios of liquidity, profitability, activity, and return on investment of sustained company are higher; while the leverage ratio is lower.The dominant influencing financial ratios toward a bankruptcy are liquidity and leverage ratios. The research finds that from ten tested ratios, Current Asset to current liabilities and total liabilities to total asset are the dominant financial ratios.